Visual studio tools for Office : using C♯ with Excel, Word, Outlook, and InfoPath - Carter, Eric (Addison-Wesley, 2005)
"With the application development community so focused on the Smart Client revolution, a book that covers VSTO from A to Z is both important and necessary. This book lives up to big expectations. It is thorough, has tons of example code, and covers Office programming in general terms-- topics that can be foreign to the seasoned .NET developer who has focused on ASP.NET applications for years. Congratulations to Eric Lippert and Eric Carter for such a valuable work!" --Tim Huckaby, CEO, InterKnowlogy, Microsoft regional director "This book covers all of the ins and outs of programming with Visual Studio Tools for Office in a clear and concise way. Given the authors' exhaustive experiences with this subject, you can't get a more authoritative description of VSTO than this book!" --Paul Vick, technical lead, Visual Basic .NET, Microsoft Corporation "Eric and Eric really get it. Professional programmers will love the rich power of Visual Studio and .NET, along with the ability to tap into Office programmability. This book walks you through programming Excel, Word, InfoPath, and Outlook solutions." --Vernon W. Hui, test lead, Microsoft Corporation "This book is an in-depth, expert, and definitive guide to programming using Visual Studio Tools for Office 2005. It is a must-have book for anyone doing Office development." --Siew Moi Khor, programmer/writer, Microsoft Corporation "We don't buy technical books for light reading; we buy them as a resource for developing a solution. This book is an excellent resource for someone getting started with Smart Client development. For example, it is common to hear a comment along the lines of, 'It is easy to manipulate the Task Pane in Office 2003 using VSTO 2005,' but until you see something like the example at the start of Chapter 15, it is hard to put 'easy' into perspective. This is a thorough book that covers everything from calling Office applications from your application, to building applications that are Smart Documents. It allows the traditional Windows developer to really leverage the power of Office 2003." --Bill Sheldon, principal engineer, InterKnowlogy, MVP "Eric Carter and Eric Lippert have been the driving force behind Office development and Visual Studio Tools for Office 2005. The depth of their knowledge and understanding of VSTO and Office is evident in this book. Professional developers architecting enterprise solutions using VSTO 2005 and Office System 2003 now have a new weapon in their technical arsenal." --Paul Stubbs, program manager, Microsoft Corporation "This book is both a learning tool and a reference book, with a richness of tables containing object model objects and their properties, methods, and events. I would recommend it to anyone considering doing Office development using the .NET framework; especially people interested in VSTO programming." --Rufus Littlefield, software design engineer/tester, Microsoft Corporation Visual Studio Tools for Office is both the first and the definitive book on VSTO 2005 programming, written by the inventors of the technology. VSTO is a set of tools that allow professional developers to use the full power of Visual Studio .NET and the .NET Framework to put code behind Excel 2003, Word 2003, Outlook 2003, and InfoPath 2003. VSTO provides functionality never before available to the Office developer: data binding and data/view separation, design-time views of Excel and Word documents inside Visual Studio, rich support for Windows Forms controls in a document, the ability to create custom Office task panes, server-side programming support against Office, and much more. Carter and Lippert cover their subject matter with deft insight into the needs of .NET developers learning VSTO. This book Explains the architecture of Microsoft Office programming and introduces the object models Teaches the three basic patterns of Office solutions: Office automation executables, Office add-ins, and code behind a document Explores the ways of customizing Excel, Word, Outlook, and InfoPath, and plumbs the depths of programming with their events and object models Introduces the VSTO programming model Teaches how to use Windows Forms in VSTO and how to work with the Actions Pane Delves into VSTO data programming and server data scenarios Explores .NET code security and VSTO deployment Advanced material covers working with XML in Word and Excel, developing COM add-ins for Word and Excel, and creating Outlook add-ins with VSTO. © Copyright Pearson Education. All rights reserved.